Exploratory studies in the use of microwave radiation to assist the extraction of pollutants from various matrices. - Zlotorzynski, Andrzej (Andrew). (University of Ottawa (Canada), 1994)
The microwave assisted extraction of organic contaminants from heterogeneous environmental solids was investigated. The mechanisms for the interaction of a microwave field with matter, and the basic equipment used in microwave processing are presented. It was found that water content is the most important factor in the transfer of microwave energy to the soil structure. The first portion of water added, adsorbs on the soil surface very strongly and the microwave field cannot move these adsorbed water molecules. As the water content increases, excitation of the loosely bound outer layers facilitates the transfer of microwave energy to the soil-water system. Other soil parameters have a insignificant role in the soil microwave heating when appliance grade microwave ovens (2.45 GHz, low energy density) are used. A simple extraction with water, acetonitrile and mixing action, proved to be fast and the most effective method for quantitative recovery of pentachlorophenol (PCP) from a spiked soil. Recovery of PCP with microwave assisted extraction provided no enhancement. An explanation for this is provided in Chapter 3. Changes in the composition of aromatic solvents in the presence of charcoal and microwave field were noted, probably resulting from free radical reactions. This poses possibly serious problems for the use of microwave radiation as a means for recovering compounds adsorbed on activated carbon. (Abstract sortened by UMI.)
Keywords: Chemistry, Organic.